INVESTIGASI NUMERIK TEMPERATUR PERMUKAAN BATERAI PACK LITHIUM - ION BERBASIS CFD DENGAN BERBAGAI GEOMETRI PERMUKAAN PADA KENDARAAN LISTRIK - Prasetyo, Bambang Teguh; Simanjuntak, Nuarson; Permanasari, Rosyida (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2026)
Electric Vehicles (EVs) use lithium-ion batteries as an effective and efficient energy storage solution. However, battery operation generates excessive heat, which can lead to fires and accidents. Maintaining the battery surface temperature is crucial to prevent thermal runaway. This study aims to numerically investigate the surface temperature of a battery pack with different geometric configurations in electric vehicles. The research method employs CFD (Computational Fluid Dynamics) simulation with various geometric configurations: first, a flat and smooth surface; second, a fin-shaped surface; and third, a wave-shaped surface. The simulation results from these different geometries will be compared with experimental data from previous research [6] to determine the optimal geometric configuration for reducing the battery pack's surface temperature.